Marie NDiaye Blankness and Recognition - Asibong, Andrew (Contemporary French and Francophone Cultures, 2013)
This is the first critical study in English to focus exclusively on the work of Marie NDiaye, born in central France in 1967, winner of the Prix Femina (2001), the Prix Goncourt (2009), shortlisted for the Man Booker International Prize (2013), and widely considered to be one of the most important French authors of her generation. Andrew Asibong argues that at the heart of NDiaye's world lurks an indefinable 'blankness' which makes it impossible for the reader to decode narrative at the level of psychology or event. Considering each of NDiaye's works (including her novels, theatre, short fiction and writing for children), Asibong assesses the aesthetic, emotional and political stakes of NDiaye's portraits of impenetrable selfhood. His book provides an original and provocative framework within which to read NDiaye as a simultaneously hybrid and hyper-French cultural figure, fascinating and fantastical practitioner of the postmodern - and reluctantly postcolonial - 'blank arts'.